Amplitude analysis of B0 → K+π-π0 and evidence of direct CP violation in B → K [ast] π decays - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We analyze the decay B0→K+π−π0 with a sample of 4.54×108 B¯¯¯B events collected by the BABAR detector at the PEP-II asymmetric-energy B factory at SLAC, and extract the complex amplitudes of seven interfering resonances over the Dalitz plot. These results are combined with amplitudes measured in B0→K0Sπ+π− decays to construct isospin amplitudes from B0→K∗π and B0→ρK decays. We measure the phase of the isospin amplitude Φ3/2, useful in constraining the Cabibbo-Kobayashi-Maskawa unitarity triangle angle γ and evaluate a CP rate asymmetry sum rule sensitive to the presence of new physics operators. We measure direct CP violation in B0→K*+π− decays at the level of 3σ when measurements from both B0→K+π−π0 and B0→K0Sπ+π− decays are combined.
Im Titel ist [ast] als Tropfensternchen dargestellt
Im Titel ist "0" und "+" und "-" hochgestellt
Gesehen am 12.08.2022